Validation of rapid antibody (IgG-IgM) test kit for SARS COV-2 infection in Qatar - Jesha Mundodan; Samina Hasnain; Hayat Khogali; Soha Shawqi Al Bayat; Dina Ali; Saif Alateeg; Hamad Al-Romaihi; Mohammed Hamad J. Al-Thani (SAGE Publishing, 2021)
Background: In response to the growing coronavirus disease 2019 (COVID-19) pandemic and the shortage of laboratory based molecular testing capacity and reagents, multiple diagnostic test manufacturers have developed rapid and easy to use devices to facilitate testing outside laboratory settings. These kits are either based on detection of proteins from SARS-CoV-2 virus or detection of antigen or human antibodies generated in response to the infection. However, it is important to understand their performance characteristics and they must be validated in the local population setting. Design and Methods: The objective is to assess the validity of the rapid test for IgG and IgM immunoglobulins compared to the current gold standard reverse transcription polymerase chain reaction (RT-PCR) test. A total of 16951 asymptomatic individuals were tested by the Ministry of Public Health track-and-trace team using both rapid immunodiagnostic test and RT-PCR as part of screening across various random settings with potential risk of community interaction prior to gradual lifting of restrictions in Qatar.  Rapid test was considered to be posiive if both IgG and IgM are positive, while only IgG/IgM positive was considered as rapid test negative. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated. Results: The sensitivity of rapid test kit was found to be 0.9%, whereas the specificity was found to be 97.8%. the PPV was found to be 0.3% whereas the NPV was found to be 99.4%. Conclusion: Based on the outcome and results of the study, it appears that the sensitivity and PPV of the rapid antibody test are low. As such, this test is not recommended for use to assist in taking clinic-based decisions or decisions related to quarantine/isolation.